2018
DOI: 10.25081/jmb.2017.v1.863
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical features of three perennial swampy plants of Poaceae, grown on the water stream banks in Nile Delta, Egypt

Abstract: The anatomical structure of plants is largely varied according to genetics as well as the environmental conditions. The present study aims to describe the anatomical features of three species of family Poaceae growing naturally in canal bank habitat namely: Arundo donax, Pennisetum setaceum and Saccharum spontaneum. These plants are referred as medicinal, grazing or fiber producing plants. Samples were obtained from the canal banks in Nile delta of Egypt. The samples were fixed in formalin-acetoalcohol and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Cells called bundle sheaths surround the vascular bundles. Arora and Kumar,[70], Gandhi and Albert,[71], and Ahmed et al[72] found similar findings in the stem of Saccharum spontaneum L., stem section of C. setigerus and stem section of I. cylinderica. The leaves of all four grasses showed upper and lower epidermis, mesophyll cells, vascular bundles, and sclerenchyma cells in their transverse sections.…”
supporting
confidence: 56%
“…Cells called bundle sheaths surround the vascular bundles. Arora and Kumar,[70], Gandhi and Albert,[71], and Ahmed et al[72] found similar findings in the stem of Saccharum spontaneum L., stem section of C. setigerus and stem section of I. cylinderica. The leaves of all four grasses showed upper and lower epidermis, mesophyll cells, vascular bundles, and sclerenchyma cells in their transverse sections.…”
supporting
confidence: 56%
“…1 × 0.5 cm). A. donax and P. australis were selected because, unlike Saccharum spontaneum, also used in ancient Egypt [31], they have a hollow stem [21,32]. The third sample (size ca.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Egypt is known to be one of the oldest native ranges of this subspecies (Gaber et al, 2009). Its habitat extends on the border of water streams within the Egyptian deserts and Nile delta (Abd El-Gawad and El-Amier, 2017). Commercially grown in tropical and subtropical areas.…”
Section: Introductionmentioning
confidence: 99%